Key Drivers of Satisfaction and Adoption Intentions for E-Government Among Chengdu’s Government Employees - Liu, Zhongming (Scholar: Human Sciences, 2025)
Purpose: This article investigates the crucial elements that significantly impact the intent to utilize E-government services among employees within government departments across three distinct regions in Chengdu, China. In the conceptual framework, trust in e-government, users’ satisfaction, perceived usefulness, perceived ease of use, facilitating conditions, social influences, and intention to use were interlinked, demonstrating a mutual influence. Research design, data, and methodology: The researcher employed a quantitative approach involving 500 participants and distributed questionnaires among government department employees across three distinct regions. The survey used a multi-stage sampling strategy to collect data, integrating judgmental and quota sampling methods. The data analysis was executed through CFA and SEM. Result: Furthermore, model fit, correlation validity, and reliability were evaluated for every element. It was found that each exogenous variable significantly influenced its respective endogenous variable, with perceived usefulness having the most important impact on the intention to use. Conclusion: This study aims to analyze factors influencing the surveys’ intention to use e-government services, thereby driving the improvement and development of e-government. It will promote e-government more effectively among the public, providing convenient services to citizens. It also enriches e-government theory, offering meaningful and useful perspectives for scholars and practitioners.